PERANCANGAN SISTEM INFORMASI PENJUALAN DAN JASA GROOMING PADA LINDA PETSHOP JAMBI - Meri Afriani; Amroni; Dwi Ayu Gusriyanti (Jurnal Informatika Dan Rekayasa Komputer(JAKAKOM), 2023)
Linda Petshop Jambi is one company located in the main town Jambi where management of sales product and grooming service data still use books. So there are often problems like Hard to manage product available quickly and accurately, often there is a mistake data services, sales or data spares used, the processing and data search, the information is less than accurate and preparing reports that cannot be resolved just in time. Hence this study aims to design system of sales and grooming service using PHP programming language and DBMS MySQL. The research using method of waterfall development system and modeling system such as use case diagram, activity diagrams, class diagram and flowchart.The result of this research is that this system is hoped to enable in processing the grooming services and sales data good calculation, a search and the preparation of reports on, so that data processing and dissemination of information gets better and regular Keywords : System, Information, Sales, Grooming Service, Web